2017
DOI: 10.1038/srep42347
|View full text |Cite
|
Sign up to set email alerts
|

Partially orthogonal resonators for magnetic resonance imaging

Abstract: Resonators for signal reception in magnetic resonance are traditionally planar to restrict coil material and avoid coil losses. Here, we present a novel concept to model resonators partially in a plane with maximum sensitivity to the magnetic resonance signal and partially in an orthogonal plane with reduced signal sensitivity. Thus, properties of individual elements in coil arrays can be modified to optimize physical planar space and increase the sensitivity of the overall array. A particular case of the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This could be potentially useful to compute depolarization rates and signal input functions from the different compartments. Alternative designs and approaches with additional coils could provide efficient whole‐body coverage with increased SNR . A caveat of our RF coil array, which uses local RF transmission and reception, is that the B 1 sensitivity could affect the dynamics of the observed signal, such as shown in Figure where the uptake appears different in each kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be potentially useful to compute depolarization rates and signal input functions from the different compartments. Alternative designs and approaches with additional coils could provide efficient whole‐body coverage with increased SNR . A caveat of our RF coil array, which uses local RF transmission and reception, is that the B 1 sensitivity could affect the dynamics of the observed signal, such as shown in Figure where the uptake appears different in each kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative designs and approaches with additional coils could provide efficient wholebody coverage with increased SNR. 31 A caveat of our RF coil array, which uses local RF transmission and reception, is that the B 1 sensitivity could affect the dynamics of the observed signal, such as shown in Figure 4 where the uptake appears different in each kidney. A more comparable uptake between the kidneys was measured with the more homogeneous volumetric coil, which reflects the small variations in perfusion expected in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Idiyatullin et al [3] proposed dental imaging with an intraoral approach by exploiting the transverse components of the B 1 field of an oriented surface RF coil with loop topology. More recently, it was reported that the RF coil Array of BC [17] 63.9 ( 1 H) Phantom SNR measurement BC [18] 128 ( 1 H) Human brain imaging BC [19] 63.9 ( 1 H) Head and neck imaging and spectroscopy BC [20] 298 ( 1 H) Human brain imaging FC [21] 25.85 ( 31 P) Phantom SNR measurement BC [22] 150 ( 13 C) Small animal metabolic imaging BC [23] 49.9 ( 31 P) Phantom SNR measurement BC [24] 105.7 ( 23 Na) Phantom SNR measurement BC [25] 74.96/298.06 ( 13 C/ 1 H) Rat brain imaging CRC loop-gap resonator [26] 63.9 ( 1 H) Temporomandibular joint imaging BC [27] ------BC [28] 298 ( 1 H) Human heart imaging BC [29] 63.9 ( 1 H) Carotid artery imaging BC, FC [30] 128 ( 1 H) Phantom SNR measurement…”
Section: Introductionmentioning
confidence: 99%
“…A concentric coil array design, adopting a BC configuration, was proposed for spatial encoding in parallel MRI as an alternative to conventional linear arrays, aiming for an imaging time reduction [17]. Chacon-Caldera et al [18] proposed a novel partially orthogonal coil pair for improving parallel imaging performance with respect to a classical configuration constituted by a BC and a single loop coil, reporting a 20% SNR increase at a target depth of 10 cm.…”
Section: Introductionmentioning
confidence: 99%